2011
DOI: 10.3382/ps.2011-01474
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic parameters, and cluster and principal components analyses of breeding values related to egg production traits in a White Leghorn population

Abstract: The objectives of this paper were to identify the phenotypic egg-laying patterns in a White Leghorn line mainly selected for egg production, to estimate genetic parameters of traits related to egg production and to evaluate the genetic association between these by principal components analysis to identify trait(s) that could be used as selection criteria to improve egg production. Records of 54 wk of egg production from a White Leghorn population were used. The data set contained records of the length:width ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 28 publications
(25 reference statements)
4
25
1
5
Order By: Relevance
“…(2000) reported high heritability for monthly egg production in Leghorn hens, which ranged from 0.18 to 0.47, and suggested that egg production should be evaluated between the age of 5 and 10 months. SAVEGNAGO et al (2011) analyzing the 17 to 30 week old laying rate of White Leghorn laying hens selected by seven generations for egg production observed a heritability of 0.15. TONGSIRI et al (2014) working with birds of the 11th generation of hens selected from the Plymouth Rock White and Rod Island Red breeds observed a heritability of 0.30 and 0.33 respectively for the characteristic egg production at 17 weeks of age.…”
Section: Resultsmentioning
confidence: 99%
“…(2000) reported high heritability for monthly egg production in Leghorn hens, which ranged from 0.18 to 0.47, and suggested that egg production should be evaluated between the age of 5 and 10 months. SAVEGNAGO et al (2011) analyzing the 17 to 30 week old laying rate of White Leghorn laying hens selected by seven generations for egg production observed a heritability of 0.15. TONGSIRI et al (2014) working with birds of the 11th generation of hens selected from the Plymouth Rock White and Rod Island Red breeds observed a heritability of 0.30 and 0.33 respectively for the characteristic egg production at 17 weeks of age.…”
Section: Resultsmentioning
confidence: 99%
“…The eggs were incubated for intervals of 15 days (3 hatches), and the birds were identified by banding. CC is a pure line mainly selected for egg and egg weight, feed conversion, hatchability, sexual maturity, fertility, viability, egg quality, and reduced body weight (Savegnago et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…SAVEGNAGO et al (2011) andVENTURINI et al (2012) pointed low heritability estimate while BESBES et al (1992) and ONI et al (2007) observed moderate heritability for egg production traits. Thus, heritability variations observed between strains UFV1 and UFV2 could be also acceptable for meat quail.…”
Section: Resultsmentioning
confidence: 96%